1806 Md. Laws 44 - (:unkn) unknown (My University, 1806)
An Act to Restrain the Evil Practices Arising From Negroes Keeping Dogs, and to Prohibit Them From Carrying Guns or Offensive Weapons, ch. 81: Prohibited "any negro or mulatto" from keeping a dog or gun, except any "free negro or mulatto" who has a license for such purpose.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES